A Transforming Growth Factor‐β and H19 Signaling Axis in Tumor‐Initiating Hepatocytes That Regulates Hepatic Carcinogenesis. Issue 4 (31st December 2018) - Zhang, Jinqiang; Han, Chang; Ungerleider, Nathan; Chen, Weina; Song, Kyoungsub; Wang, Ying; Kwon, Hyunjoo; Ma, Wenbo; Wu, Tong
Abstract : Functions of transforming growth factor‐β (TGF‐β) in the liver vary depending on specific cell types and their temporal response to TGF‐β during different stages of hepatocarcinogenesis (HCG). Through analysis of tumor tissues from hepatocellular carcinoma (HCC) patients, we were able to cluster hepatic epithelial cell‐derived TGF‐β gene signatures in association with distinct clinical prognoses. To delineate the role of hepatic epithelial TGF‐β signaling in HCC development, we used an experimental system in which tumor‐initiating hepatocytes (TICs) were isolated from TGF‐β receptor II floxed mice ( Tgfbr2 fl/fl ) and transplanted into syngeneic C57BL/6J mice by splenic injection. Recipient mice were then administered Cre‐expressing adenovirus (Ad‐Cre) to inactivate Tgfbr2 in transplanted TICs. After latency, Tgfbr2‐inactivated TICs formed larger and more tumor nodules in recipient livers compared to TICs without Tgfbr2 inactivation. In vitro analyses revealed that treatment of cultured TICs with TGF‐β inhibited expression of progenitor cell factors (including SRY (sex determining region Y)‐box 2 [Sox2]). RNA sequencing (RNA‐seq) analysis identified H19 as one of the most up‐regulated long noncoding RNA (lncRNA) in association with Tgfbr2 inactivation in TICs. Tgfbr2 inactivation by Ad‐Cre led to a 5‐fold increase of H19 expression in TICs. Accordingly, TGF‐β treatment reduced H19 expression. We observed that forced overexpression of Sox2 in TICs increased transcription of H19, whereas knockdown of Sox2 decreased it. Furthermore, depletion of H19 reduced the progenitor property of TICs in vitro and decreased their tumorigenic potential in vivo . Finally, we observed a low level of H19 mRNA expression in human HCC tissues from patients with the epithelial TGF‐β gene signature in association with favorable prognosis. Conclusion: Our findings describe a TGF‐β and H19 signaling axis by Sox2 in TICs that importantly regulates HCG.